Does smile help detect the UK's price leadership change after MiFID? - Mike Buckle (International Review of Economics and Finance, 2023)
We investigate intraday realised volatility, trading volume, and information transmission following a series of changes to the Markets in Financial Instruments Directive (MiFID) in the UK. We find that multilateral trading facilities attract order flows from the London Stock Exchange (LSE) and hence introduce new dynamics to market provisions, such as volatility and information transmission. In addition, the structure of the order books and market depth changed after the introduction of MiFID in the UK. However, our novel study conveying smile patterns of volatility and volume suggests that the LSE continues to lead the rest of the multilateral venues. This shows that although MiFID has led to market segmentation, there is still clear price discovery among multilateral trading facilities.